2013
DOI: 10.1080/10615806.2012.757306
|View full text |Cite
|
Sign up to set email alerts
|

The role of athletes' pain-related anxiety in pain-related attentional processes

Abstract: Numerous researchers have highlighted the social determinants of athletes' attitude toward pain, yet little is known about the role of cognitive processes and emotions that are related to pain in sport endeavors. There is evidence, in a dot probe paradigm, that individuals with chronic pain selectively orient their attention toward pain-related stimuli, but no studies have differentiated between the two attentional processes of hypervigilance that are evident in athletes: facilitated detection of threat and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
11
0
3
Order By: Relevance
“…Anxiety disorder is a comorbid condition of chronic pain (Bardel et al, 2013;Lucchetti et al, 2013). Analgesics and anxiolytics are currently used to manage pain and anxiety symptoms.…”
Section: Chronic Pain and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety disorder is a comorbid condition of chronic pain (Bardel et al, 2013;Lucchetti et al, 2013). Analgesics and anxiolytics are currently used to manage pain and anxiety symptoms.…”
Section: Chronic Pain and Anxietymentioning
confidence: 99%
“…However, chronic pain (also referred to as persistent pain) persists for a prolonged period and is usually caused by various diseases or abnormal conditions (Siddall and Cousins, 2004). Chronic pain is highly associated with mood disorders, such as anxiety and depression (Bardel et al, 2013;Blackburn-Munro and Blackburn-Munro, 2001;Rouwette et al, 2012). Patients suffering from chronic pain also experience emotional disorders, such as depression, associated with additional pain complaints and impairment (Smith, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies, trials with reaction times lower than 150 ms or higher than 2000 ms were excluded from analyses [9,105,106]. In addition, trials where participants indicated the wrong location of the probe (error trials) were excluded.…”
Section: Data Reduction and Statistical Analysesmentioning
confidence: 99%
“…There is evidence that patients with high pain-related anxiety and patients with chronic musculoskeletal pain selectively orient their attention toward painful stimuli, reflecting difficulty disengaging from painful stimuli rather than hypervigilance [3,9,28]. Among patients with chronic back pain, greater awareness of symptoms seems to increase disability in the presence of catastrophic thinking [7,13].…”
Section: Discussionmentioning
confidence: 99%